The efforts to reduce the academic procrastination of students on grade V elementary school - Ratih Dewi Puspitasari; Suwarjo Suwarjo (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
The student learning process must be accompanied by a diligent, disciplined and obedient attitude in order the learning process runs optimally. The learning time management becomes one of the problems that will impact students. The effect of the problem of time management is the phenomenon of the students’ tendency to delay in completing the tasks. The performance of students who delay in completing the tasks cannot maximize the student academic achievement. Academic procrastination is a situation where the students do not want to try to complete a task within the time limitation as scheduled. The particular study described the various efforts made by teachers to reduce the student academic procrastination. The research type was descriptive research using descriptive qualitative approaches and case study methods. The subjects were fifth-grade teachers who had efforts to solve the academic procrastination. Data collection techniques were interviews, observation, and documentation. Data analysis technique used interactive analysis which consisted of three components, namely (1) Data reduction, (2) Data display, and (3) Verification. The findings showed that the efforts made by the teacher to reduce the student academic procrastination are through daily activities, diaries, motivations, achievement tables and good communication between teachers and parents.